2016
DOI: 10.15560/12.2.1874
|View full text |Cite
|
Sign up to set email alerts
|

Bird diversity of the Amrutganga Valley, Kedarnath, Uttarakhand, India with an emphasis on the elevational distribution of species

Abstract: A unique aspect of montane birds is the elevational stratification they show in their distribution, but in the Himalayas, a subset of the species show elevational migration, making bird communities on these mountains especially dynamic. Thus, understanding the elevational distribution and movement of species across seasons is important to fully understand broad-scale community patterns. In this study, we compile a comprehensive checklist of birds along a 2,300 m Hima­layan elevational gradient in the Amrutgang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…Birds in the Himalayas exhibit two distinct phenologies of elevational distribution. Elevational migrants occur at low elevation for most of the year (eight to nine months), but move to higher elevations (2000 -4000 m or even higher) during the three-to four-month summer to breed [18]. These two elevational movement strategies are widely known in birds and have been hypothesized to arise due to limits on cold tolerance in winter [19], food availability [20] and predation [21].…”
Section: Introductionmentioning
confidence: 99%
“…Birds in the Himalayas exhibit two distinct phenologies of elevational distribution. Elevational migrants occur at low elevation for most of the year (eight to nine months), but move to higher elevations (2000 -4000 m or even higher) during the three-to four-month summer to breed [18]. These two elevational movement strategies are widely known in birds and have been hypothesized to arise due to limits on cold tolerance in winter [19], food availability [20] and predation [21].…”
Section: Introductionmentioning
confidence: 99%
“…Some investigators have suggested a link between snow at higher elevation and altitudinal migration to lower elevations, but no one has actually tested this hypothesis (King and Wales , O'Neil and Parker , Tomback , Hendricks and Swenson , Dixit et al. ). The general assumption is that snow represents a challenge for birds, with the results of some studies suggesting the inability to recover seeds stored in the ground as the specific mechanism (King and Wales , Tomback , Hendricks and Swenson ).…”
Section: Resultsmentioning
confidence: 99%
“…1 a Phylogenetic relationships among bird species used in the analysis following [ 46 ]. Elevational distributions are from Dixit et al [ 31 ] and Rasmussen and Anderton [ 41 ]. Dotted vertical lines represent sampling locations.…”
Section: Methodsmentioning
confidence: 99%
“…We classified each sampled species as either an elevational migrant (EM status = 1) where almost all individuals migrate to significantly lower elevations or as sedentary (EM status = 0) were species that are consistently found in their breeding range in the winter in our study site. Information on elevational movement and distribution was obtained from a field survey [ 31 ] in our study site and Rasmussen and Anderton [ 41 ]. The first analysis consisted of generalized linear mixed models (GLMMs, function glmer in lme4; Bates et al [ 42 ]) to assess whether individual infection status with Plasmodium , Haemoproteus and Leucocytozoon was influenced by elevation, bird migration strategy and season, as fixed effects, and bird taxonomy (species nested in genus and genus nested in family) as a random effect.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation